1991
DOI: 10.1177/095632029100200504
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Isolates from an Immunocompromised Patient who Failed to Respond to Acyclovir Treatment Express Thymidine Kinase with Altered Substrate Specificity

Abstract: Ten sequential post-treatment herpes simplex virus type 1 (HSV-1) isolates were obtained from an immunocompromised patient whose infection, during prolonged treatment, became unresponsive to acyclovir (ACV). Of the ten isolates, eight later isolates were resistant in vitro to ACV and ganciclovir (DHPG), but remained sensitive to 9-[3-D-arabinofuranosyladenine (ara-A) and phosphonoformate (PFA). Biochemical characterization of plaque-purified clones of the resistant isolates revealed an altered thymidine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
(51 reference statements)
1
20
0
Order By: Relevance
“…They are predominantly TK deficient and would therefore not be susceptible to PCV. Two HSV clinical isolates with ACV-resistant DNA polymerase mutations have been described (Parker et el., 1987;Collins et el., 1989;Sacks et al, 1989), as well as several TK substrate specificity mutants (Hill et et., 1991;Nugier et al, 1991). The laboratory-derived ACV-resistant polymerase mutants and the TK substrate specificity mutant reported here were all found to be cross-resistant to PCV, although one laboratory-generated ACV-resistant polymerase mutant that was sensitive to PCV has been 4 4 minimal reduction in virus recovery from the primary site.…”
Section: Discussionmentioning
confidence: 96%
“…They are predominantly TK deficient and would therefore not be susceptible to PCV. Two HSV clinical isolates with ACV-resistant DNA polymerase mutations have been described (Parker et el., 1987;Collins et el., 1989;Sacks et al, 1989), as well as several TK substrate specificity mutants (Hill et et., 1991;Nugier et al, 1991). The laboratory-derived ACV-resistant polymerase mutants and the TK substrate specificity mutant reported here were all found to be cross-resistant to PCV, although one laboratory-generated ACV-resistant polymerase mutant that was sensitive to PCV has been 4 4 minimal reduction in virus recovery from the primary site.…”
Section: Discussionmentioning
confidence: 96%
“…Isolate 11 contained a substitution at nt 527 that resulted in an amino acid substitution at codon 176 within the putative nucleoside-binding site as well as two other changes (codons 42 and 89) associated with gene polymorphism (21,25). The amino acid change (Arg176Glu) has been previously reported in a laboratory-derived HSV-1 mutant (12) and in ACV-resistant HSV-1 isolates (30). A 3G-for-3C substitution was observed in isolate 12 at positions 175 to 179 within the proposed ATPbinding site (42).…”
Section: Susceptibility Of Hsv Clinical Isolates To Acvmentioning
confidence: 99%
“…Darby et al have proposed a preliminary model for the active center of the HSV type 1 (HSV-1) TK enzyme including three distinct regions: an ATP-binding site (amino acids 51 to 63), a nucleoside-binding site (amino acids 168 to 176), and amino acid 336 (12). Indeed, single-point mutations in one or more of these conserved regions have been found in ACVresistant HSV isolates (16,20,25,30,41,42). Furthermore, Sasadeusz et al have identified mutational hot spots consisting of frameshift mutations within homopolymer nucleotide stretches of G's and C's (41).…”
mentioning
confidence: 99%
“…The loss in affinity was compared with the wild-type the solved crystal structures [9, 10, 23], is incomplete as the essential Mg 2ϩ ion is absent. Therefore, modeling work has been previously, exhibit the same mutations as those obtained in vitro, namely A168→T and R176→Q [33,34]. performed to account for the lack of structural evidence.…”
Section: Materials [Methyl-1′2′-3 H]thymidine (100ϫ130 Ci/mmol) Wasmentioning
confidence: 99%